Time to Loss of Response following Withdrawal of Ixekizumab in Patients with Moderate-to-Severe Psoriasis - Kim Papp; Carle Paul; C. Elise Kleyn; Yu-Huei Huang; Tsen-Fang Tsai; Christopher Schuster; Celine El Baou; Agoston Toth; Elisabeth Riedl; Ulrich Mrowietz (Medical Journals Sweden, 2022)
In clinical practice, interruption of treatment may not result in immediate cessation of disease control, and some patients even experience sustained treatment response following treatment interruption. This post hoc analysis of UNCOVER-1 and -2 Phase 3 clinical trials characterized the time to loss of treatment response in patients with psoriasis who responded to ixekizumab through a 12-week treatment period, and who were then re-randomized to placebo for the following 48 weeks. For those with static Physician Global Assessment [sPGA]0/1 and Psoriasis Area and Severity Index [PASI]90 at Week 12, the median time to loss of PASI90 was 16.1 weeks (95% confidence interval 12.7-16.4). For those with PASI100 at Week 12, the median time to loss of PASI100 was 12.1 weeks (95% confidence interval 9.0-13.0). A small subset of patients maintained high levels of disease control through Week 60. This study adds to the growing body of evidence on sustained treatment response following treatment interruption.